Analysis For Precipitation Climate prediction - Ferraz, Simone Erotildes Teleginski; Souto, Roberto; Dias, Pedro; Velho, Haroldo Fraga de Campos; Ruivo, Heloisa (Ciência e Natura, 2013)
An evaluation for the precipitation climatology for the Rio Grande do Sul state (Brazil) is performed. The BRAMS code is feeded with boundary conditions from the CPTEC-INPE global circulation model (GCM). The simulated precipitation for this region in Brazil presented a climate standard diferent from the observations. An spectral analysis on the wind was carried out to explain the desagreement.